Adaptive epigenetic response of glutathione (GSH)-related genes against lead (Pb)-induced toxicity, in individuals chronically exposed to the metal. (April 2021) - Devóz, Paula Pícoli; Reis, Mariana Bisarro dos; Gomes, Willian Robert; Maraslis, Flora Troina; Ribeiro, Diego Luis; Antunes, Lusânia Maria Greggi; Batista, Bruno Lemos; Grotto, Denise; Reis, Rui Manuel; Barbosa Jr., Fernando; Barcelos, Gustavo Rafael Mazzaron
Abstract: It is well known that one of the most outstanding adverse effects related to lead (Pb) exposure is oxidative stress; moreover, recent findings suggest that disturbances of the redox status of cells are associated with epigenetic responses, and metabolism of glutathione (GSH) plays an important role in this process. This study aimed to assess Pb exposure on % methylation of GSH-related genes' promoter regions (%CH3 -CpG) and their influence on biomarkers of oxidative stress, in workers exposed to the metal. One hundred nine male workers participated in the study; ICP-MS determined blood lead levels (BLL); biochemical parameters related to redox status, named GSH, glutathione peroxidase (GPX) and glutathione-S-transferase (GST) were quantified by UV/Vis spectrophotometry. Determination of %CH3 -CpG of genes GCLC, GPX1, GSR, and GSTP1 were done by pyrosequencing. Inverse associations were seen between BLL and %CH3 -CpG- GCLC, and %CH3 -CpG- GSTP1 . Moreover, metal exposure did not impact GSH, GPX, and GST; however, negative associations were observed between %CH3 -CpG- GPX1 and %CH3 -CpG- GSTP1, and the activities of GPX and GST, respectively. Taken together, our results give further evidence about adaptive epigenetic response to avoid oxidative damage induced by Pb exposure, allowing a better understanding of the molecular mechanisms related to the metal toxicity. Graphical abstract: Image 1 Highlights: Pb exposure induces disturbances of epigenetic status, in exposed individuals. Pb exposure decreases the % methylation of promoter region of GSH-related genes. Epigenetic feedback of GSH-related genes against Pb-induced oxidative stress. Pb-induced epigenetic responses are related to exposure levels of the metal.